2020
DOI: 10.1128/msystems.00200-20
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Stool Metaproteomics: Method and Application to Human Specimens

Abstract: Stool-based proteomics is capable of significantly augmenting our understanding of host-gut microbe interactions. However, compared to competing technologies, such as metagenomics and 16S rRNA sequencing, it is underutilized due to its low throughput and the negative impact sample contaminants can have on highly sensitive mass spectrometry equipment. Here, we present a new stool proteomic processing pipeline that addresses these shortcomings in a highly reproducible and quantitative manner. Using this method, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Our initial experiment involved the establishment of an optimal sample preparation workflow applied to the mouse fecal metaproteome. In this context, we assessed two sample preparation steps that are commonly employed in metaproteomic studies: 1) the usage of LSC 19 , 24 , 34 versus nLSC; 24 , 35 and 2) in-solution digestion 19 , 22 versus filter-aided sample preparation (FASP) 20 , 21 (Figure S1A, Table S1). The resulting LC-MS/MS data were processed using the MaxQuant software.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial experiment involved the establishment of an optimal sample preparation workflow applied to the mouse fecal metaproteome. In this context, we assessed two sample preparation steps that are commonly employed in metaproteomic studies: 1) the usage of LSC 19 , 24 , 34 versus nLSC; 24 , 35 and 2) in-solution digestion 19 , 22 versus filter-aided sample preparation (FASP) 20 , 21 (Figure S1A, Table S1). The resulting LC-MS/MS data were processed using the MaxQuant software.…”
Section: Resultsmentioning
confidence: 99%
“…We used quantitative metaproteomics to measure the expressed proteins and functions, because we were particularly interested in the functional state of the microbiomes, which is best assessed at the protein level instead of DNA level (16S rRNA gene 7 sequencing or metagenomics) 26 . Moreover, recent development of MS-based deep metaproteomics approaches [26][27][28] allows rapid and comprehensive profiling of the functions of the cultured microbiomes in this study. In agreement with previous FMT and animal studies 20,21 , we did not observe obvious detrimental effects on the functional profiles of the microbiomes frozen up to a year.…”
Section: Discussionmentioning
confidence: 99%
“…The LSC approach also leads to more consistent identifications and as a result fewer missing values, which is a general and extensive problem in metaproteomic datasets. Regarding the topic of reproducible protein identification and quantification, a recent metaproteomic study demonstrated the use of Tandem Mass Tag (TMT) approach in human stool samples [22].…”
Section: Both Lsc and Nlsc Methods Have Merits For The Metaproteomic Analysis Of Murine Faecal Samplesmentioning
confidence: 99%
“…Many studies have reported increased protein identification due to laboratory optimisation for the analysis of metaproteome samples [19][20][21][22][23]. In humans, different sample preparation methodologies have been shown to result in significant changes in the taxonomic composition and functional activities representated [19,24,25].…”
Section: Introductionmentioning
confidence: 99%